Century‐scale causal relationships between global dry/wet conditions and the state of the Pacific and Atlantic Oceans - Qiaohong Sun; Chiyuan Miao; Amir AghaKouchak; Qingyun Duan (Geophysical Research Letters)
Abstract The Granger causality test is used to examine the effects of the El Niño–Southern Oscillation (ENSO), the Pacific Decadal Oscillation (PDO), and the North Atlantic Oscillation (NAO) on global dry/wet conditions. The results show robust relationships between dry/wet conditions and the ocean states, as assessed through a multi‐index (standardized precipitation evapotranspiration index and standardized precipitation index) and multiscale (3 months and 12 months) evaluation. The influence of ENSO events is widespread, dominating about 38% of the global land surface (excluding Antarctica). Southern and western North America, northern South America, and eastern Russia are influenced by the PDO. The NAO influences not only dry/wet conditions in Europe but also dry/wet conditions in northern Africa. Similarly, climate variability in southern Europe and northern Africa may be due to the concurrence of the ENSO and the NAO. Knowledge of the spatial influence of ocean states on global dry/wet conditions is valuable for improving drought and flood forecasting.